Evidence for sialyl glycoconjugates as receptors for Bordetella bronchiseptica on swine nasal mucosa. - Ishikawa, H (1987)
The nature of the receptors for Bordetella bronchiseptica was investigated by using the in vitro adherence assay system. The results indicated that sialyl glycoconjugates acted as receptors on swine nasal mucosa. These results were obtained by two independent approaches: inhibition of epithelial cell adherence with sialic acid-containing compounds but not with compounds lacking sialic acid residues and loss of adherence after treatment of epithelial cells with periodate or neuraminidase. B. bronchiseptica seems to have strong affinity for mucin. This may help the bacterium to colonize the mucosal surfaces of the swine nasal cavity.